2017
DOI: 10.1186/s40635-017-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial oxidative stress correlates with left ventricular dysfunction on strain echocardiography in a rodent model of sepsis

Abstract: BackgroundRecognition of cardiomyopathy in sepsis can be challenging due to the limitations of conventional measures such as ejection fraction (EF) and fractional shortening (FS) in the context of variable preload and afterload conditions. This study correlates myocardial function using strain echocardiography (SE) with cardiomyocyte oxidative stress in a murine model of sepsis.MethodsC57BL/6J mice were randomized into control (n = 10), sham (n = 25), and a cecal ligation and puncture (CLP) (n = 33) model of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 39 publications
(43 reference statements)
2
38
0
2
Order By: Relevance
“…[73] Additionally, changes in myocardial strain have been shown to correlate with the upregulation of in ammatory cytokines and mitochondrial dysfunction in the form of an increased in mitochondrial ROS. [72] In our study, eCIRP worsened both longitudinal and radial cardiac strain, providing direct evidence that eCIRP causes cardiac dysfunction in neonatal sepsis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…[73] Additionally, changes in myocardial strain have been shown to correlate with the upregulation of in ammatory cytokines and mitochondrial dysfunction in the form of an increased in mitochondrial ROS. [72] In our study, eCIRP worsened both longitudinal and radial cardiac strain, providing direct evidence that eCIRP causes cardiac dysfunction in neonatal sepsis.…”
Section: Discussionsupporting
confidence: 67%
“…[38,71] Myocardial strain can identify sepsis-associated cardiac dysfunction even in the presence of a normal ejection fraction, which can occur with decreased cardiac work and does not accurately re ect cardiac dysfunction. [72] In a meta-analysis of adult patients with sepsis, increased (i.e., less negative) global longitudinal strain values were associated with mortality; this nding was not seen with ejection fraction -the most commonly used parameter to evaluate adult cardiac function in sepsis. [73] Additionally, changes in myocardial strain have been shown to correlate with the upregulation of in ammatory cytokines and mitochondrial dysfunction in the form of an increased in mitochondrial ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The data from the present and previous studies 33,34 suggest that oxidative stress can be involved in the etiology of cardiovascular pathologies. Result of much work confirms the close relation of the endogenous antioxidant defense mechanisms and ionic current changes.…”
Section: Discussionsupporting
confidence: 64%
“…LPS-induced myocardial depression (measured as peak tension generated by myocardial contraction) coincides with decreased activity of GPx, the most abundant antioxidant enzyme in myocardium, and decreased levels of GSH, the most important thiol in combating oxidative stress [ 11 ]. Moreover, strain echocardiography identified septic cardiomyopathy which correlates with reduced expression of key mitochondrial ROS scavengers [ 110 ]. In animals, it has been found that both superoxide dismutase and glutathione peroxidase activities, in cardiac mitochondria, decrease (as much as 40% and 70% compared to animals without sepsis) early after sepsis induction and remain at lower levels throughout the first 24 hours after LPS challenge.…”
Section: Reactive Speciesmentioning
confidence: 99%